Three-dimensional smoothed particle hydrodynamics simulation for injection molding flow of short fiber-reinforced polymer composites - He, L.; Lu, G.; Chen, D.; Li, W.; Lu, Chunsheng (IOP Publishing, 2017)
This paper investigates the three-dimensional (3D) injection molding flow of short fiber-reinforced polymer composites using a smoothed particle hydrodynamics (SPH) simulation method. The polymer melt was modeled as a power law fluid and the fibers were considered as rigid cylindrical bodies. The filling details and fiber orientation in the injection-molding process were studied. The results indicated that the SPH method could effectively predict the order of filling, fiber accumulation, and heterogeneous distribution of fibers. The SPH simulation also showed that fibers were mainly aligned to the flow direction in the skin layer and inclined to the flow direction in the core layer. Additionally, the fiber-orientation state in the simulation was quantitatively analyzed and found to be consistent with the results calculated by conventional tensor methods.